Media as a Construct of the Modern Discursive Personality: Methodology of the Values-Based Approach - Skrynnik, Yuliia (Communication Today, 2023)
This research focuses on the study of the theoretical and methodological grounds of a values-based approach to the typology of discursive personalities. The concept of values and their modern variations are described in the article, as well as the influence of the modern media on their alterations in society. The methodology of a values-based approach is grounded in the article which presupposes setting the typology of modern discursive personalities. Their characteristics are described taking into account the influence of the media. The division of the discursive personalities into three basic groups – participant, attractor, creator – is presented as optimal regarding the basic needs of modern society. From this standpoint the notion of the positioning of a personality in discourse facilitates clarifying the choice of a values-based approach to the typology of modern discursive personalities. A values-based approach within discourse studies extends the neo-anthropocentric paradigm in modern linguistics as well as contributes to the socio-cognitive approach to discourse studies.